2018
DOI: 10.1111/jocn.14146
|View full text |Cite
|
Sign up to set email alerts
|

Oral health matters for the nutritional status of older persons—A population‐based study

Abstract: Nursing staff involved in care for older people should be aware of the importance of including regular oral health check-ups in their work. There is also a need for nursing staff members and oral health professionals to exchange knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 41 publications
4
33
2
Order By: Relevance
“…In addition, almost one-fifth of the long-term care residents were malnourished according to MNA, which is in line with a recent meta-analysis by Cerada and colleaques (35). The association between OS and poor nutritional status found in the current study has also been found in previous studies (23)(24)33,36). For example, a recent Dutch study (23) showed that older nursing home residents, who suffered from at least one oral health problem (artificial teeth problems, chewing problems,…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, almost one-fifth of the long-term care residents were malnourished according to MNA, which is in line with a recent meta-analysis by Cerada and colleaques (35). The association between OS and poor nutritional status found in the current study has also been found in previous studies (23)(24)33,36). For example, a recent Dutch study (23) showed that older nursing home residents, who suffered from at least one oral health problem (artificial teeth problems, chewing problems,…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 42% of the residents suffered from at least one OS, which is in line with previous Finnish research in institutional settings (33,34) and with a Swedish population-based study (24). The latter found that 42% of the older population had oral health problems with their voices, lips, oral mucosa, tongues, gums, teeth, saliva or swallowing.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study using ROAG‐J established relationship between oral health problems and nutritional status in older people with nursing care needs. The authors highlight the importance of routine oral health check‐ups in nursing care for older people (Lindmark, Janssonn, Lannering, & Johansson, ). However, in daily nursing care, there is limited knowledge about the extent to which measures are planned.…”
Section: Introductionmentioning
confidence: 99%
“…Oral care is a neglected part of essential nursing care at home, in nursing homes and hospitals (Coker, Ploeg, Kaasalainen, & Carter, ; Everaars, Jerkovic‐Cosic, van der Putten, Pretty, & Brocklehurst, ; Lewis, Edwards, Whiting, & Donnelly, ; de Lugt‐Lustig et al, ; Miegel & Wachtel, ; Sloane et al, ). Impaired oral health has a negative impact on nursing‐sensitive outcomes such as food intake and subsequently undernutrition (De Marchi, Hugo, Hilgert, & Padilha, ; Huppertz, van der Putten, Halfens, Schols, & de Groot, ; Lindmark, Jansson, Lannering, & Johansson, ; Sheiham et al, ), perform communication and subsequent quality of life (Coleman, ), and infections (Bartzokas et al, ; Quinn et al, ; Sato et al, ; Sjogren, Nilsson, Forsell, Johansson, & Hoogstraate, ). To diminish these negative consequences and increase nutritional status and quality of life, oral health should be improved in hospitalised patients.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired oral health limits people's ability to eat, smile and speak, psychosocial well‐being and quality of life (Coleman, ). Furthermore, several studies have shown the association between undernutrition and oral health problems (De Marchi et al, ; Huppertz et al, ; Lindmark et al, ; Sheiham et al, ). When patients experience pain or limitations throughout chewing and swallowing, a lower nutritional intake can be a consequence.…”
Section: Introductionmentioning
confidence: 99%